Study on Growth Rate and Seaweed Eucheuma spinosum And Euchema cottoni in Waters of Kutuh Village, South Kuta Sub-District, District of Badung-Bali - Wiyanto, Dwi Budi (Journal of Environment)
Seaweed is a non-fish fishery commodity. The market demand for seaweed, both from the domestic and foreign markets has a bright future as a trade commodity on the international market. Bali is one of the islands of seaweed producers in Indonesia. Seaweed production in Bali in 2008, decreased to 15.2% compared to that in 2007. The purpose of this study was to determine how big the difference between the growth rate of E. cottonii seaweed and that of E. spinosum. Seaweed cultivation was conducted using raft off the base (off bottom method) of 2 units with the size of 5 x 2.5 meters each. Spacing of each seed was 25 -30 cm. Seed weight of seaweed E. cottonii and E. spinosum is equal to 100 grams. Maintenance time was for 40 days, and the sampling was done once every 10 days as many as 10 samples of seaweed. The results showed that seaweed E. cottonii had faster growth compared with E. spinosum. Seaweed daily growth of the species E. spinosum in the first 10 days was faster than the seaweed of the species E. cottonii. However, the second 10 days to the third 10 days E. cottonii seaweed growth was faster than E. spinosum. The average weight of Euheuma cottonii for 40 days planting was 189.29 grams while the average weight of Eucheuma spinosum was 185.55 grams. Water condition in the location of research was still in the normal range for the growth of two species of seaweed cultivated.